Cyber victimization and well-being in adolescents: The sequential mediation role of forgiveness and coping with cyberbullying - Eroglu, Yüksel; Peker, Adem; Cengiz, Serkan (Frontiers in Psychology, 2022)
Cyber victimization is an important problem among adolescents and it can have negative effects on well-being. However, efforts to increase the well-being of cyber victims have been increasing in recent years. It is important to uncover the underlying mechanisms that may affect the well-being of cyber victims. This study used the transactional model of stress and coping theory as a conceptual framework and proposed that hope and coping strategies are sequential mediators for the effects of cyber-victimization on well-being. A total of 337 students aged between 14 and 19 participated in this research (Mage = 16.56). We used the Cyber Victimization Scale, the Forgiveness Scale for Adolescents, the Scale for Coping with Cyber Bullying, and the Well-Being Scale as data collection tools. Pearson Correlation was used to examine the relationships between cyber victimization, coping with cyberbullying, well-being and forgiveness. Afterward, measurement modeling was done using AMOS 22.0 and the PROCESS macro was used for hypothesis testing. The results show that there is a negative relationship between cyber victimization and forgiveness, coping with cyberbullying, and well-being. In addition, forgiveness and coping with cyberbullying was found to have a sequential mediating effect on the relationship between cyber victimization and well-being. The research results provide information on how to increase the well-being of adolescents experiencing cyber victimization.